The Effect of Health Belief Model- Based Training (HBM) on Self- Medication among the Male High School Students - Ehsan Movahed; Davood Shojaei zadeh; Morad ali Zarei pour; Zohre Arefi; Faramarz Sha ahmadi; Mahboobe Ameri (Iranian Association of Health Education and Health Promotion, 2014)
Background: Self-medication is a kind of treating without enough knowledge about the symptoms, diseases and the related reactions or behaviors, which individuals try to solve their problem without the aid of physicians. Due to their presence in the critical period such as adolescence, students are of utmost importance. The aim of this study was to determine the effect of education based on Health Belief Model (HBM) on self-medication among high school students of Manoujan County in Kerman Province. Methods: This RCT study conducted in 2010 250 individuals (boys from high school of Manujan) participated and samples were divided into two groups, case and control. Sampling was conducted randomly in 4 schools and in each school 2 classes were chosen. Children of any two classes was aggregated and randomly divided into cases and controls. The method of data collecting was an organized questionnaire based on the Health Belief Model (HBM), sensitivity, intensity, perceived benefits/gains and obstacles, guidance and a checklist of students' performance toward the self-medications. The questionnaire and checklist were completed for both groups prior to doing the learning intervention, and after 2 months of learning intervention in both groups. In order to analyze the data chi-square test, t-test and paired t-test were used by SPSS18 software. Results: The mean ages of case and control group were 16.96 and 15.93, respectively. Mean score of knowledge and all of the other parts had a significant difference. Before intervention, the level of perceived sensitivity, obstacles and performance in the field of self was less than its average and the level of knowledge, intensity and perceived gains in the field of using medicines forwardly was more than its average but after the learning intervention, there was a significant difference between these two groups in all mentioned variables and the performance of students in self-medication had decreased. Conclusion: With the increase in knowledge, the sensitivity, intensity and perceived score, and the perceived obstacles of students toward using medicine decreased. This shows the effect and performance of Health Belief Model (HBM) among students in relation to self-medication. Therefore, it is recommended to emphasize more on the importance of educating and promoting the knowledge level in relation to self-medication. To finally achieve the optimal performance, we also need to study the cultural, family backgrounds and effective factors on attitude and knowledge.